The Interfacial Transition Zone in Alkali-Activated Slag Mortars - San Nicolas, Rackel; Provis, John L. (Frontiers in Materials, 2015)
The interfacial transition zone (ITZ) is known to strongly influence the mechanical and transport properties of mortars and concretes. This paper studies the ITZ between siliceous (quartz) aggregates and alkali activated slag binders in the context of mortar specimens. Backscattered electron images (BSE) generated in an environmental scanning electron microscope (ESEM) are used to identify unreacted binder components, reaction products and porosity in the zone surrounding aggregate particles, by composition and density contrast. X-ray mapping is used to exclude the regions corresponding to the aggregates from the BSE image of the ITZ, thus enabling analysis of only the binder phases, which are segmented into binary images by grey level discrimination. A distinct yet dense ITZ region is present in the alkali-activated slag mortars, containing a reduced content of unreacted slag particles compared to the bulk binder. The elemental analysis of this region shows that it contains a (C,N)-A-S-H gel which seems to have a higher content of Na (potentially deposited through desiccation of the pore solution) and a lower content of Ca than the bulk inner and outer products forming in the main binding region. These differences are potentially important in terms of long-term concrete performance, as the absence of a highly porous interfacial transition zone region is expected to provide a positive influence on the mechanical and transport properties of alkali-activated slag concretes.